Right ventricular performance in essential hypertension after beta-blockade. - Ferlinz, J (1981)
Recent studies indicate that right ventricular performance is impaired even in uncomplicated systemic hypertension. Because of widespread use of beta-blockade in essentially hypertension, it is possible that such treatment often further depresses right ventricular contractility. To test this premise, and to evaluate the changes induced by different beta-adrenoceptor blocking agents on the contractility of right ventricular myocardium, 20 patients with essential hypertension were divided into two groups on a double-blind randomised basis, and maintained on oral oxprenolol or propranolol for five weeks. Cardiac catheterisation and right ventricular cineangiography were performed at the beginning and again at the end of the five week period. Right ventricular end-diastolic volume index did not change significantly in either group. In contrast, right ventricular end-systolic volume index increased, and right ventricular ejection fraction significantly decreased after chronic beta-blockade. Cardiac index decreased in both groups, but these changes were not statistically significant. When the intergroup differences were compared for all measured indices none of the changes between the two groups was statistically significant. Despite its intrinsic sympathomimetic activity, oxprenolol therefore impairs right ventricular performance to an extent nearly equal to that of propranolol. Moreover, right ventricular contractility is clearly diminished after the institution of beta-blockade in hypertensive patients--an effect that has until now been thought to be limited to the left side of the heart. Great caution must therefore be exercised when beta-blockade is initiated in patients with severely abnormal right ventricular function, because frank right ventricular decompensation may result.